Attitudes toward teaching among graduates of the National Teacher Training Center for the Health Professions - Alcazaren, Francis Jerome B. (2002)
Attitudes of teachers toward teaching is one of the factors that influences the quality of education. Yet, little attention is given to attitudes when it comes to educational researches. This study aims to look into the attitudes toward teaching of the MHPEd graduates. In shedding the light on the attitudes of MHPEd graduates toward teaching, it is hoped that this study will contribute to the development of better health professions educators and better teaching as well. A questionnaire was sent to all 55 graduates. There were 35 who responded, giving the survey a response rate of 70 percent. Descriptive statistical methods were used initially to summarize and present a picture of the collected data. The Sign Test, a statistical method was used to detect perceived changes in attitude before and after the attainment of the MHPEd degree. The Sign Test was utilized to determine if there were significant differences in attitudes toward teaching among graduates of the NTTC-HP and the following variables: academic rank, years of teaching, profession, civil status and gender. The results of the survey showed that the MHPEd graduates realized the importance of planning after MHPEd degree. It was also found that more attention to the communication between teacher and student, and among students are given by MHPEd graduates. An increase in consciousness was also noted with regard to time spent counseling the students, their availability for consultation and the kind of help they extend to the students. The concern for students learning was also heightened after MHPEd degree. And lastly there was increased willingness to continue learning whether through formal education, learning from colleagues or through more self-experience. The results revealed that attitudes toward teaching (pertaining to planning, communicating, assessment, counseling, providing resources, self-continuing education) among MHPEd graduates varied according to gender, profession, academic rank. The study presents attitudes of the MHPEd graduates toward teaching. Hopefully this study can contribute to the development of a valid instrument for attitude assessment of MHPEd graduates. This will allow the NTTC-HP to study the attitudes development of its graduates and its impact on the MHPEd course, health professionals and the health situation of the country.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Attitudes; Teaching